An Extensive Study of Thermo-electric Effect - Mukul Chandra Das (Chemical Engineering Diponegoro University, 2019)
In well known thermo-electric effect (i.e. in thermo-couples generally used in college laboratories) the maximum temperature difference between the junctions approaches 100oC resulting in small magnitude of the current and potential difference produced. These are in the micro range. To have higher currents and potential differences a different type of experiment is to be performed.In this work an experiment has been proposed where thermo-electric effect is observed more prominently for different temperatures of a hotter conductor while keeping another conductor fixed at lower temperature (generally the room temperature) making the temperature difference too high resulting in the current and potential difference to increase. Experiment has also been performed to increase the thermo-electric power by joining a number of thermo-couples.